The Relationship of Self Care with Disabilities in People with Leprosy in the South Jakarta - Firsty, Lucia (STIKep PPNI Jawa Barat, 2022)
Aims: Leprosy can cause health problem for sufferers. Although it does not cause death directly, leprosy can cause disability that can affect the productivity, social life, economy and future of the sufferer. Efforts are needed to prevent further disability by taking regular self-care. Self-care can be done individually or in groups. Methods: This study uses a quantitative approach with a cross sectional design. Sampling using all leprosy patients who were recorded at the registration at 4 Public Health Centers in the South Jakarta area. The total population is 157 people with leprosy. The method of data collection is carried out by interviews and questionnaire. Results: This study provides results that self-care does not stand alone in influencing disability in leprosy patients. But there is an interaction between self-care with the attitude of the patient in performing self-care and the reaction to the treatment given to leprosy sufferers. The variables of self-care, attitudes and reactions to leprosy are variables related to disability in leprosy patients at the Public Health Centers in the South Jakarta area. The most dominant variable related to disability in leprosy patients was self-care (p=0.001 and OR=3.381). The OR value for self-care is 3.38, so people with leprosy who do not perform self-care have 3 times the risk of disability. Conclusion: The need for self-care carried out by leprosy patients both individually and in groups to prevent disability.